Shibboleths of Grief: Paul Muldoon’s “The Triumph” - Wit Pietrzak (Lodz University Press, 2021)
The essay explores Paul Muldoon’s elegy for the fellow Northern Irish poet Ciaran Carson with a view to showing that “The Triumph” seeks to evoke a ground where political, cultural and religious polarities are destabilized. As the various intertextual allusions in the poem are traced, it is argued that Muldoon seeks to revise the notion of the Irish shibboleths that, as the poem puts it, “are meant to trip you up.” In lieu of this linguistic and political slipperiness, “The Triumph” situates Carson’s protean invocations of Belfast and traditional Irish music as the new shibboleths of collectivity.